Pengaruh Penggunaan Aplikasi Belajar Anak “Icando” Terhadap Perkembangan Kognitif Anak Usia Dini Dalam Berfikir Simbolik Di TK Darul Fikri - Resiana, Rani Surya; Hayati, Dian (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2025)
This research is motivated by the lack of cognitive development of early childhood in symbolic thinking among students at Darul Fikri Kindergarten. In facing the era of industrial revolution 4.0, the use of technology, especially in learning, is important. In Indonesia, technology-based applications, such as Icando, have been introduced as an interactive learning tool for early childhood. The Icando children's learning application is one method that can be used to improve cognitive development. This research aims to describe the influence of using the Icando children's learning application on the cognitive development of young children in symbolic thinking. The population of this study were students, parents and teachers at Darul Fikri Kindergarten, Sucinaraja District, Garut Regency with a sample size of 22 people. This research uses a quantitative descriptive method with a correlation design, and analysis of the coefficient of determination is also carried out to determine how much contribution the analysis will make after it is carried out. The results of data analysis in this study show that partially, the Children's Learning Application "Icando" has a significant influence on the cognitive development of young children in symbolic thinking. The results of the coefficient of determination show that 66.9% of children's cognitive development in symbolic thinking is influenced by the use of the Icando children's learning application, while the remaining 33.1% is influenced by other factors, such as the learning methods applied at Darul Fikri Kindergarten. Keywords: Early childhood education, learning applications, "Icando" Children's Learning Application, cognitive development, symbolic thinking